Penerapan Analisis Swot Sebagai Dasar Penentuan Strategi Peningkatan Kinerja Pt. Bank X Di Surabaya - Lintang Venusita; Pramita Kartika Sari (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2011)
AbstractPerformance is the result or degree of the person's overall success for a certain period in the task compared with a range of possibilities, such as working standards, targets or goals or criteria are predetermined and mutually agreed. Researchers have identified a phenomenon that occurs in the PT. Bank X can see how the application of a SWOT analysis as a basis for determining the performance improvement strategy. The purpose of this study was to determine the strategy to improve the performance of PT. Bank X. Of acquisition score internal-external quadrant is known that the position of PT. Bank X is located at coordinates (-0.44; -0.26) are in a position or is in quadrant IV Defensive strategy (WT) is an unfortunate situation for PT. Bank X because the direction of defensive strategy indicates that the PT. Bank X has the environmental threats of the temporary position is relatively weak and should strive to minimize weaknesses and avoid threats that occur. Some suggestions are presented, among others, development and training to improve skills and quality, product innovation and improve the quality of the service to customers, adding to the facilities and infrastructure to support the activities of banks, the selection of candidates before the merger partners.